PREPARATION OF AVIATION INDUSTRY TRANSITION ON COVID-19 FROM PANDEMIC TO ENDEMIC PHASE: A REVIEW - Zakaria, Izatul Husna; Mohammad, Nur'Jila; Abashah, Aidanazima; Alshuaibi, Mohammad Said Ibrahim; Othman, Adilah; Ahmad, Nurazwa; Abu Yaziz, Mohd Fathi; Muslim Diekola Akanmu, Muslim Diekola Akanmu (JPB, 2023)
Purpose: The aim of this study is to examine the Malaysian government's actions towards the aviation industry to deal with the Covid-19 pandemic and the transition phase from pandemic to endemic. Transition phase refers to a temporary period before the country could fully enter the endemic phase which is subject to an announcement by the World Health Organisation (WHO). Theoretical framework:The study on air transport affected by pandemic and industry action toward the endemic phase. This study refers to the conceptual framework for emergency department design in a pandemic by Aujirapongpan (2023): Relationship between state, hospital and ED in pandemic preparedness planning and response. Design/methodology/approach: The approach used qualitative research that are observation and literature review. Findings: The results demonstrate the Malaysian government's actions during the transition period from pandemic to endemic. Restrictions on travel between areas cause the public to be unable to move at will, causing passengers to be unable to buy plane tickets. The government's actions have indeed had an impact on the airline company's income. Among the significant effects are the workers who were laid off in the era of the pandemic. At the same time, the government is also trying to help airlines financially to survive while waiting for the endemic period. The Malaysian government does not have a specific framework for the airline industry to face the